Phenotypic and morphometric characterization of local muscovy ducks raised in West Africa, Benin - Daouda Libanio; Lionel Kinkpe; Tchilabalou Bouassi; Milognon Boris Behingan; Naqash Goswami; Ogechi E. Kadurumba; Anthony Pokoo-Aikins; Frederic Mankpondji Houndonougbo; Christophe Archille Armand Chrysostome (PLoS ONE, 2025)
The Muscovy duck ( Cairina moschata ) is a vital poultry species for rural livelihoods in Benin, yet no prior scientific study has documented its phenotypic and morphometric characteristics in the country. This study presents the first comprehensive characterization of Muscovy ducks raised across three agroecological zones of southern Benin, aiming to establish a foundational reference for sustainable breeding and conservation. A total of 406 adult ducks (260 females and 146 males) from 93 smallholder farms were assessed for both qualitative and quantitative traits. Significant sexual dimorphism was observed, with males exhibiting larger body dimensions than females (P < 0.05). A wide range of plumage patterns was recorded, dominated by white (58%), along with black, ash, and the first report of rare blue eye coloration. Beak and skin colours were mostly pink (66%) and white (73%), respectively; traits that may serve as important identifiers for local genetic lines. Notably, most morphometric traits varied significantly across colour morphs and agroecological zones, reflecting rich phenotypic diversity. Ducks with spotted white and grey plumage had superior measurements, while other colour groups excelled in specific traits such as thoracic cage width and leg length. Strong positive correlations were found between body weight and body length (r = 0.73), and leg length and chest height (r = 0.80). These results offer valuable insights for local producers and lay the groundwork for targeted selection, genetic improvement, and future molecular research on indigenous duck populations in Benin.